The Description of Quality of Life of Elderly During the Pandemic COVID-19 at Nursing Home of Bondowoso - Yahtarita ulfia Adisiwi; Latifa Aini Susumaningrum; Tantut Susanto; Hanny Rasni; Fahruddin Kurdi; Roro Dewi Qudsyiyah; Khoirun Nasikhin (Nursing and Health Sciences Journal (NHSJ), 2021)
During the COVID-19 pandemic, the elderly were required to reduce direct interactions with people around them. So that, it affected the psychological condition and social relations of the elderly which caused a decrease in their quality of life (QOL). This study aimed to analyze the QOL among elders during the pandemic COVID-19 at the Nursing Home of Bondowoso. The method used in this study was quantitative research with a descriptive design conducted at the Nursing Home of Bondowoso from April until May 2021. 48 elders participated in this study selected by consecutive sampling technique. Data were collected through self-report interviews using a self-administered questionnaire used to identify characteristics of the elderly and WHOQOL-BREF to identify their QoL. The one-sample Kolmogorov-Smirnov's test was used to reach the aim of this study. The result showed that the QOL among elders during the COVID-19 pandemic underwent a significant with Md(25-75)=50(44-52); Z=0,152; p-value 0,007. It can be concluded that the QOL of elders during COVID-19 underwent a significant Quality of life and the majority of elderly experience moderate QOL. Therefore, to improve the QOL, the elderly must maintain good communication with others, and conduct regular physical activity.